Effect of A Limited Amount of D-Sorbitol on Pitch and Mechanical Properties of Cellulose Nanocrystal Films - Xiao-Yao Wei (MDPI AG, 2021)
A cellulose nanocrystal (CNC) suspension can form liquid crystal films with unique self-assembly behaviors. This gives CNC films a special iridescence, which has potential in many aspects, but the brittleness of pure CNC films limits their application. In this work, we propose a simple physical mixing method to obtain CNC film by adding D-sorbitol as a plasticizer. We first found that low D-sorbitol content (less than 6 wt% in CNC/DS composite solution) did not make a significant difference compared with pure CNC films in optical performance and, at the same time, the mechanical properties of the CNC films were improved. The various low contents of D-sorbitol can be well dispersed in CNC aqueous suspension, and the wavelength of the selectively reflected phenomenon is relatively stable and slightly decreased at 5 nm for concentrations from 0 to 6%. This phenomenon is opposite to that generally reported, where the wavelength of the selective reflected phenomenon increases obviously with the increase in plastic content. The pitch of the chiral structure decreased from 406 to 362 nm with an increase in D-sorbitol concentration. When the content of D-sorbitol reached 4%, the tensile strength, elongation at break, and Young modulus increased to 39.9 Mpa, 3.00%, and 2.99 GPa, respectively.